ANALISIS PERBANDINGAN PERFORMA DATABASE SQL DB ORACLE DENGAN NOSQL DB MONGODB - Imelda Audina (Prosiding Seminar Nasional Indonesia, 2025)
Databases have become an essential component of data management systems. In the ever-evolving information age, information and technology professionals are faced with the question of choosing a database that suits their diverse business and application needs. DBMS is divided into two types, namely relational database (SQL DB) and non-relational database (NoSQL DB). This research uses Oracle as a relational database and MongoDB as a non-relational database. The mechanism of data processing and storage is the difference between SQL DB and NoSQL DB. To find out the differences, especially in the query response from both, testing is needed. The database uses the gravity_book database from the cust_order table with a total data of 7550 rows and consists of 5 columns. Testing is done by applying four DML command operations in order to access and manipulate data from the cust_order table, namely by SELECT (reading data), UPDATE (updating data), INSERT (adding data), DELETE (deleting data) by limiting the number of different data records (750, 1500, 2550, 3000). This research aims to analyze the performance comparison between SQL DB Oracle and NoSQL DB MongoDB from the resulting query speed. The results show that the fastest response time for all test query commands is Oracle, while MongoDB ranks second after Oracle.